Investing in the health workforce in Kenya: trends in size, composition and distribution from a descriptive health labour market analysis. (25th August 2022) - Okoroafor, Sunny C; Kwesiga, Brendan; Ogato, Julius; Gura, Zeinab; Gondi, Joel; Jumba, Nakato; Ogumbo, Teresa; Monyoncho, Maureen; Wamae, Annah; Wanyee, Mutile; Angir, Meldah; Almudhwahi, Mona Ahmed; et al.
Abstract : Investing in the health workforce to ensure universal access to qualified, skilled and motivated health workers is pertinent in achieving the Sustainable Development Goals (SDGs). The policy thrust in Kenya is to improve the quality of life of the population by investing to improve health service provision and achieving universal health coverage. To realise this, the Ministry of Health undertook a Health Labour Market Analysis with to generate evidence on the relationship between supply, demand and need of the health labour force. In the context of supply, Kenya has a total of 189 932 health workers in 2020 with 66% being in the public sector and 58%, 13% and 7% being nurses, clinical officers and doctors, respectively. The density of doctors, nurses and clinical officers per 10 000 in Kenya in 2020 was 30.14, which represents about 68% of the SDG index threshold of 44.5 doctors, nurses and midwives per 10 000 population. Findings indicates that Kenya needs to align future production in terms of cadre and quantity to the population health needs. Achieving this requires a multisectoral approach to ensure apposite quantity and mix of intakes into training institutions based on the health needs and ability to employ health workers produced.